A Treasure Trove of Insights: Sixty Years of JCR Research on Negotiation and Mediation. (October 2017) - Druckman, Daniel; Wall, James A.
Six decades of JCR research on negotiation and mediation are celebrated in this article. Starting with the earliest articles on these topics, we trace the development of recurring themes. The themes serve to organize a review of findings reported in the journal. The research on negotiation covers processes and conditions that occur prior to, during, and at the end of negotiation. The work on mediation provides insights into mediator approaches and impacts. This article concludes with suggestions for integrating and better understanding of the negotiation and mediation processes.